Performance of an allele‐level multi‐locus HLA genotype imputation tool in hematopoietic stem cell donors from Quebec - Ferradji, Abdelhakim; D'Souza, Yasmin; Saw, Chee Loong; Oualkacha, Karim; Richard, Lucie; Sapir‐Pichhadze, Ruth (Immunity, Inflammation and Disease, 2017)
Introduction Donor‐recipient HLA compatibility is an important determinant of transplant outcomes. Allele‐group to allele‐level imputations help assign HLA genotypes when allele‐level genotypes are not available during donor selection. Methods We evaluated the performance of HaploStats, an allele‐level multi‐locus HLA genotype imputation tool from the National Marrow Donor Program, in a cross‐sectional study including hematopoietic stem cell donors (HSCD) from Quebec, Canada. A total of 144 self‐identified Caucasian HSCD genotyped at the allele‐group and allele‐level for HLA‐A, ‐B, ‐C, ‐DRB1, and ‐DQB1 loci were studied. We compared allele‐level genotypes imputed by HaploStats to those obtained by the reference standard, sequenced‐based typing (SBT). Results Imputation performance, determined by allele‐level genotype recall (fraction of matching imputed and sequenced genotypes) was 97%, 96%, 95%, 84%, and 81% for HLA‐A, ‐B, ‐C, ‐DRB1, and ‐DQB1 loci, respectively. Our sample deviated from Hardy‐Weinberg equilibrium only at the HLA‐DRB1 locus. Residual ambiguity, determined by typing resolution scores (TRS), was greatest for HLA class II loci (average TRS 0.65 and 0.80 for DRB1 and DQB1, respectively). In contrast, average TRS of 0.88, 0.84, and 0.92 was observed for HLA‐A, ‐B, and ‐C, respectively. Conclusions HLA allele imputation from ambiguous genotypes demonstrate satisfactory prediction accuracy for HLA class I but modest prediction accuracy for HLA class II loci in self‐identified Caucasian HSCD from Quebec. While consideration of high‐resolution allele and haplotype frequencies in the Quebec population may improve the performance of available allele‐level multi‐locus genotype imputation tools in Quebec, this study suggests that genotyping at the first two field level should be conducted whenever possible. We evaluated the performance of HaploStats, an allele‐level multi‐locus HLA genotype imputation tool from the National Marrow Donor Program, in hematopoietic stem cell donors (HSCD) from Quebec, Canada. HLA allele imputation from ambiguous genotypes demonstrated satisfactory accuracy for HLA class I but modest accuracy for HLA class II loci in self‐identified Caucasian HSCD.